A method for preparing conductive ceramic with controllable resistivity
By using ceramic slurry as the core material in conductive ceramics, combined with low -temperature plasma discharge and multi -stage high -temperature sintering technology to form a multi -layered ceramic matrix, solve the problem of shape change and contraction in the sintering process, and realize the high strength and available ceramics and available can Control conductive performance.
Patent Information
- Application Number
- CN202411139412.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-08-20
AI Technical Summary
Existing conductive ceramics are prone to deformation and shrinkage during the sintering process, affecting their strength and conductivity, and it is difficult to achieve a controllable resistivity.
Using ceramic slurry as the core material, through low-temperature plasma discharge treatment and multi-stage high-temperature sintering technology, combined with materials such as starch and aminated nanographite sheets, a multi-layer structure ceramic matrix is formed, and the sintering process and material composition are optimized to improve the strength and strength of the ceramic. Conductive properties.
The high intensity and good conductive performance of ceramics have been realized, and they have controllable resistance at the same time, which solve the problem of shape change and contraction during sintering, and improve the overall performance of the ceramics.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive ceramics, and in particular to a method for preparing conductive ceramics with controllable resistivity. Background Art
[0002] Alumina ceramics are a type of ceramic material with aluminum oxide as the main component. They have good conductivity, mechanical strength and high temperature resistance. As a widely used ceramic, they are also widely used as electronic ceramic raw materials in the electronics industry because of their superior thermal conductivity and conduction properties. With the development of ceramic technology, the demand and performance requirements for ceramics are constantly increasing, and their fine craftsmanship has also made great progress. However, the ceramic sintering process is an indispensable process for ceramic materials. Due to a series of reasons such as the temperature difference of the furnace, the density difference of the green body, and gravity, certain deformations will be formed during the ceramic sintering process, causing the shrinkage of the ceramic material itself, affecting the strength and subsequent use.
[0003] Conductive ceramics are new functional special ceramics, and they are a type of basic materials. They have all the properties of ceramics, such as anti-oxidation, high temperature resistance, corrosion resistance, low cost, good mechanical properties, etc., and they also have the conductive properties of a metal state. Conductive ceramics can produce electrons (holes), ions (vacancies), etc. under certain conditions, and can produce directed charge movement under the action of an electric field. At present, titanium-based compounds are introduced into alumina ceramics to form a conductive phase, but the performance improvement is limited, and with the increase in the amount of titanium-based compounds added, although the resistivity of the ceramic can be greatly reduced, it also affects the strength of the ceramic. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a controllable resistivity conductive ceramic to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a controllable resistivity conductive ceramic, comprising the following preparation steps:
[0006] (1) Alumina balls, titanium nitride and silicon dioxide are fully mixed in a mass ratio of 1-99:1-99:0.1-5 to obtain ceramic powder;
[0007] (2) Ceramic powder, anhydrous ethanol and alumina grinding balls are added into a ball mill equipped with a low-temperature plasma discharge device in a mass ratio of 3:3:4. The ball mill is carried out at 50-100 rpm for 6 hours under an inert atmosphere. The low-temperature plasma discharge device is turned on every 2 hours and treated at 400-800 W for 1-5 minutes. The mixture is then poured into a low-speed stirring tank at a stirring speed of 5-10 r / min. A binder in an amount of 0.01-0.05 times the mass of the ceramic powder is added and the stirring time is 20-40 hours to obtain a ceramic slurry.
[0008] (3) Starch and water are prepared into a concentration of 15-20 wt%, heated at 70-100°C and 30 rpm for 1-2 h, 0.08-0.1 times the mass of starch glycidyl methacrylate and 0.3-0.5 times the mass of starch in 20% sulfuric acid are added, stirring is continued for 4-6 h, and then 0.08-0.1 times the mass of starch amino-modified nanographite sheets are added, stirring is continued for 8-10 h, after cooling to room temperature, 0.08-0.3 times the mass of starch zirconium oxychloride and 0.08-0.1 times the mass of starch nickel acetate are added, stirring is continued for 1-3 h at 60 rpm, and then transferred to a 4°C refrigerator for 24 h to obtain a gel;
[0009] (4) Inject the ceramic slurry into mold 1, freeze it at -25°C for 3 hours to obtain the core layer, and put it into the center of mold 2. The size of mold 2 is larger than that of mold 1. Fill the blank gap of mold 2 with gel, freeze it at -25°C for 10 hours, and then freeze-dry it at -50°C for 24 hours to obtain a ceramic matrix with the core layer wrapped by the gel layer;
[0010] (5) Place the ceramic substrate in a muffle furnace, heat it to 400-430°C at a rate of 2-5°C / min, pressurize it to 1.5-10MPa at a rate of 2-10Pa / s, maintain the pressure for 1-2h, then release the pressure at a rate of 2-10Pa / s, heat it to 800-860°C at a rate of 5-10°C / min, transport the atomized droplets through a carrier gas, keep the temperature for 3-5h, then place it in a vacuum furnace, heat it to 1200-1400°C at a rate of 8-10°C / min, and obtain a conductive ceramic.
[0011] Furthermore, in step (1), the diameter of the alumina balls is 0.05-2 mm, the particle size of the titanium nitride is 8-12 μm, and the particle size of the silicon dioxide is 80-200 nm.
[0012] Furthermore, the inert atmosphere in step (2) is nitrogen or argon.
[0013] Furthermore, the binder in step (2) is polyvinyl alcohol.
[0014] Furthermore, in step (2), the viscosity of the ceramic slurry is controlled within a range of 100-500 cps.
[0015] Furthermore, the starch in step (3) is rice starch.
[0016] Furthermore, the preparation method of the amino-modified nano-graphite sheet in step (3) is as follows: nano-graphite sheets with a diameter of 1 to 100 μm and a thickness of 5 to 200 nm are selected and mixed with a 70 wt% ethanol aqueous solution to form a concentration of 0.1 wt%, the temperature is controlled at 60°C, a modifier is added in an amount of 5 to 20% by mass of the nano-graphite sheet, the mass ratio of γ-aminopropyltriethoxysilane to lauryl alcohol polyoxyethylene ether in the modifier is 1:1, the solid is filtered out after stirring at 1000 rpm for 2 hours, and dried at 80°C for 4 hours to obtain the amino-modified nano-graphite sheet.
[0017] Furthermore, in step (4), the radius difference between the core layer and the gel layer is controlled within a range of 0.1 to 5 mm.
[0018] Furthermore, in step (5), the carrier gas is a mixture of H2O and O2, the volume percentage of H2O is 1.3-8 vol%, and the carrier gas is 50-300 mL / h.
[0019] Furthermore, the atomized droplets in step (5) are prepared by ultrasonic atomization of 5 wt % LaCl 3 · 7H 2 O-methanol at 20-60 kHz.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] (1) The present invention uses ceramic slurry as the core material, performs the first curing treatment, controls the curing time, makes the core material semi-solid, retains a certain viscosity, is conducive to the subsequent combination of the gel layer and the core material, ensures the overall stability and strength of the ceramic, and then wraps a layer of gel on the outer layer of the core material, performs the second curing treatment, and finally performs high-temperature sintering. This ceramic has a strong load capacity, higher strength than traditional ceramics, and better conductivity;
[0022] (2) The ceramic slurry is composed of three different particle sizes of alumina, titanium nitride and silicon dioxide, and is ground in a low-temperature plasma environment. By mixing various particle sizes, dense accumulation of various particles is achieved during the molding process, thereby improving the strength of the green body, reducing the possibility of deformation, and improving the overall yield rate. Micro-nano-scale titanium nitride and silicon dioxide can be embedded in the gaps between alumina ball particles, which can greatly improve the problem of alumina shrinkage during sintering and improve the mechanical properties to a certain extent. At the same time, the present invention adjusts the resistivity of the ceramic by adjusting the addition amount of the three powders to achieve controllable resistivity of the ceramic; and low-temperature plasma can effectively activate the inorganic powder, which is beneficial to the full adhesion and bonding of the core material and the gel layer, thereby reducing the shrinkage rate and ensuring the integrity of the morphology;
[0023] (3) The gel layer uses starch as the main gel material. In an acidic environment, methyl methacrylate glycidyl ether is added. The epoxy group is easily opened to form alcohol hydroxyl groups, which are cross-linked with sugar molecules through hydroxyl groups to form a gel skeleton. Aminated nanographite sheets are added as skeleton structure supports to effectively reduce the volume shrinkage of the gel layer during sintering and avoid collapse, thereby ensuring the mechanical strength of the ceramic. At the same time, the amino group can combine with some alcohol hydroxyl groups to enhance the skeleton structure and indirectly improve the mechanical strength of the ceramic. Finally, zirconium ions and nickel ions are doped to obtain a zirconium / nickel / starch-based gel layer.
[0024] (4) High-temperature sintering is divided into three stages. The first stage is pressurized heat treatment, which promotes the mutual diffusion of elements between the gel layer and the core material interface, so that the interface changes from chemical bonding to mechanical occlusion and chemical bonding at the same time, thereby improving the strength of the ceramic and reducing the tendency of the ceramic surface to crack or fall off. In this stage, the starch is initially carbonized to form a high-strength, conductive carbon skeleton layer; the second stage is diffusion heat treatment, which uses lanthanum ion solution to atomize and penetrate the ceramic, which can effectively optimize the microstructure of the core ceramic and the outer gel layer, improve the stability of the crystal, and thus improve the mechanical strength of the ceramic. At the same time, a mixed atmosphere of H2O and O2 is used to thermally decompose zirconium and nickel and combine with lanthanum to form a zirconium-nickel-lanthanum-carbon crystal structure, which greatly improves the conductive properties of the gel layer, thereby forming a uniform and continuous conductive path on the surface and inside of the ceramic. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe the method in detail. The test methods of various indicators of the conductive ceramics prepared in the following examples are as follows:
[0027] The resistivity test uses a volume resistance tester, the test temperature is 25°C, and the test humidity is 50%;
[0028] The flexural strength was tested using a flexural strength tester using a three-point flexural strength test method.
[0029] Example 1; (1) Alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm were fully mixed in a mass ratio of 1:98.9:0.1 to obtain a ceramic powder;
[0030] (2) Ceramic powder, anhydrous ethanol, and alumina grinding balls were added into a ball mill equipped with a low-temperature plasma discharge device in a mass ratio of 3:3:4. The ball mill was milled at 80 rpm for 6 h in an argon atmosphere. The low-temperature plasma discharge device was turned on every 2 h and treated at 600 W for 3 min. The mixture was then poured into a low-speed stirring tank at a stirring speed of 5 r / min. Polyvinyl alcohol (0.03 times the mass of the ceramic powder) was added and stirred for 35 h to obtain a ceramic slurry.
[0031] (3) Prepare rice starch and water to a concentration of 15 wt %, heat at 80 ° C and 30 rpm for 1.5 h, add 0.09 times the mass of rice starch glycidyl methacrylate and 0.3 times the mass of rice starch in 20% sulfuric acid, continue stirring for 5 h, then add 0.1 times the mass of rice starch amino-modified nanographite sheets, continue stirring for 10 h, cool to room temperature, add 0.18 times the mass of rice starch zirconium oxychloride and 0.09 times the mass of rice starch nickel acetate, stir at 60 rpm for 3 h, and transfer to The gel was obtained by standing in a refrigerator at 4°C for 24 hours. The preparation method of the amino-modified nano-graphite sheet was as follows: a nano-graphite sheet with a diameter of 10 μm and a thickness of 100 nm was selected and mixed with a 70 wt% ethanol aqueous solution to form a concentration of 0.1 wt%, the temperature was controlled at 60°C, a modifier with a mass ratio of 10% of the mass of the nano-graphite sheet was added, and the mass ratio of γ-aminopropyl triethoxysilane to lauryl alcohol polyoxyethylene ether in the modifier was 1:1. After stirring at 1000 rpm for 2 hours, the solid was filtered out and dried at 80°C for 4 hours to obtain the amino-modified nano-graphite sheet.
[0032] (4) injecting the ceramic slurry into mold 1, freezing at -25°C for 3 hours to obtain a core layer, and placing it in the center of mold 2. The size of mold 2 is larger than that of mold 1. Filling the blank gap of mold 2 with gel, freezing at -25°C for 10 hours, and then freeze-drying at -50°C for 24 hours to obtain a ceramic matrix with a core layer wrapped by a gel layer; the radius difference between the core layer and the gel layer is controlled to be 2.2 mm;
[0033] (5) The ceramic substrate is placed in a muffle furnace, the temperature is increased to 425°C at a rate of 2°C / min, the pressure is increased to 6.8MPa at a rate of 2Pa / s, the pressure is maintained for 1h, and then the pressure is released at a rate of 8Pa / s, the temperature is increased to 860°C at a rate of 5°C / min, the atomized droplets are transported by a carrier gas, the temperature is maintained for 4.5h, and then the ceramic substrate is placed in a vacuum furnace and the temperature is increased to 1350°C at a rate of 10°C / min to obtain a conductive ceramic; the carrier gas is a mixture of H2O and O2, the volume percentage of H2O is 2.5vol%, and the carrier gas is 220mL / h; the atomized droplets are prepared by ultrasonic atomization of 5wt% LaCl3·7H2O-methanol at 20kHz.
[0034] Example 2; The difference between Example 2 and Example 1 is that the mass ratio of alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm is 1:96.5:2.5, and the remaining steps are the same as Example 1.
[0035] Example 3; The difference between Example 3 and Example 1 is that the mass ratio of alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm is 1:94:5, and the remaining steps are the same as Example 1.
[0036] Example 4; The difference between Example 4 and Example 1 is that the mass ratio of alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm is 50:49.9:0.1, and the remaining steps are the same as Example 1.
[0037] Example 5; The difference between Example 5 and Example 1 is that the mass ratio of alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm is 50:47.5:2.5, and the remaining steps are the same as Example 1.
[0038] Example 6; The difference between Example 6 and Example 1 is that the mass ratio of alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm is 50:45:5, and the remaining steps are the same as Example 1.
[0039] Example 7; The difference between Example 7 and Example 1 is that the mass ratio of alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm is 98.9:1:0.1, and the remaining steps are the same as Example 1.
[0040] Example 8; The difference between Example 8 and Example 1 is that the mass ratio of alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm is 96.5:1:2.5, and the remaining steps are the same as Example 1.
[0041] Example 9; The difference between Example 9 and Example 1 is that the mass ratio of alumina balls with a ball diameter of 0.5 mm, titanium nitride with a particle size of 10 μm, and silicon dioxide with a particle size of 100 nm is 94:1:5, and the remaining steps are the same as Example 1.
[0042] Example 10; The difference between Example 10 and Example 9 is that the amount of zirconium oxychloride added is 0.08 times the mass of starch, the amount of nickel acetate added is 0.08 times the mass of starch, the radius difference between the core layer and the gel layer is controlled at 0.1 mm, and the remaining steps are the same as Example 9.
[0043] Example 11; The difference between Example 11 and Example 9 is that the amount of zirconium oxychloride added is 0.13 times the mass of starch, the amount of nickel acetate added is 0.085 times the mass of starch, the radius difference between the core layer and the gel layer is controlled at 1.1 mm, and the remaining steps are the same as Example 9.
[0044] Example 12; The difference between Example 12 and Example 9 is that the amount of zirconium oxychloride added is 0.24 times the mass of starch, the amount of nickel acetate added is 0.095 times the mass of starch, the radius difference between the core layer and the gel layer is controlled at 3.6 mm, and the remaining steps are the same as Example 9.
[0045] Example 13; The difference between Example 13 and Example 9 is that the amount of zirconium oxychloride added is 0.3 times the mass of starch, the amount of nickel acetate added is 0.1 times the mass of starch, the radius difference between the core layer and the gel layer is controlled at 5 mm, and the remaining steps are the same as Example 9.
[0046] Comparative Example 1: The difference between Comparative Example 1 and Example 9 lies in the difference between steps (1) and (2). Step (1) is changed to: aluminum oxide, titanium nitride and silicon dioxide are fully mixed in a mass ratio of 94:1:5 to obtain ceramic powder; step (2) is changed to: ceramic powder, anhydrous ethanol and aluminum oxide grinding balls are added in a mass ratio of 3:3:4 to a ball mill equipped with a low-temperature plasma discharge device, and ball milled at 80 rpm under argon atmosphere until D50 is 1 μm. The low-temperature plasma discharge device is turned on every 2 hours, and treated at 600 W for 3 minutes, and then poured into a low-speed stirring tank with a stirring speed of 5 r / min, and polyvinyl alcohol 0.03 times the mass of the ceramic powder is added, and the stirring time is 35 hours to obtain a ceramic slurry. The remaining steps are the same as those in Example 9.
[0047] Comparative Example 2: The difference between Comparative Example 2 and Example 9 is that step (2) is different. Step (2) is changed to: ceramic powder, anhydrous ethanol and alumina grinding balls are added to a ball mill in a mass ratio of 3:3:4, and ball milled at 80 rpm for 6 h under argon atmosphere. The mixture is then poured into a low-speed stirring tank at a stirring speed of 5 r / min, and polyvinyl alcohol (0.03 times the mass of the ceramic powder) is added. The stirring time is 35 h to obtain a ceramic slurry. The remaining steps are the same as those in Example 9.
[0048] Comparative Example 3: The difference between Comparative Example 3 and Example 9 is that glycidyl methacrylate is not added, and the remaining steps are the same as Example 9.
[0049] Comparative Example 4: The difference between Comparative Example 4 and Example 9 is that no amino-treated nanographite sheets are added, and the remaining steps are the same as Example 9.
[0050] Comparative Example 5: The difference between Comparative Example 5 and Example 9 is that zirconium oxychloride is not added, and the remaining steps are the same as Example 9.
[0051] Comparative Example 6: The difference between Comparative Example 6 and Example 9 is that nickel acetate is not added, and the remaining steps are the same as Example 9.
[0052] Comparative Example 7: The difference between Comparative Example 7 and Example 9 is that step (5) is different. Step (5) is changed to: placing the ceramic substrate in a muffle furnace, heating it to 860°C at 5°C / min, transporting the atomized droplets through a carrier gas, and heat-treating it for 4.5 hours. Then, placing it in a vacuum furnace, heating it to 1350°C at 10°C / min, and obtaining a conductive ceramic; the carrier gas is a mixture of H2O and O2, the volume percentage of H2O is 2.5 vol%, and the carrier gas is 220 mL / h; the atomized droplets are obtained by ultrasonic atomization of 5 wt% LaCl3·7H2O-methanol at 20 kHz, and the remaining steps are the same as Example 9.
[0053] Comparative Example 8: The difference between Comparative Example 8 and Example 9 is that step (5) is different. Step (5) is changed to: placing the ceramic substrate in a muffle furnace, heating it to 425°C at 2°C / min, pressurizing it to 6.8MPa at 2Pa / s, maintaining the pressure for 1h, then releasing the pressure at 8Pa / s, and then placing it in a vacuum furnace, heating it to 1350°C at 10°C / min to obtain a conductive ceramic. The remaining steps are the same as Example 9.
[0054] Comparative Example 9: The difference between Comparative Example 9 and Example 9 is that step (5) is different. Step (5) is changed to: placing the ceramic substrate in a muffle furnace, heating it to 425°C at 2°C / min, pressurizing it to 6.8MPa at 2Pa / s, maintaining the pressure for 1 hour, then releasing the pressure at 8Pa / s, heating it to 860°C at 5°C / min, delivering a carrier gas at a flow rate of 220mL / h, maintaining the temperature for 4.5 hours, and then placing it in a vacuum furnace, heating it to 1350°C at 10°C / min to obtain a conductive ceramic; the carrier gas is a mixture of H2O and O2, and the volume percentage of H2O is 2.5vol%. The remaining steps are the same as Example 9.
[0055] Comparative Example 10: The difference between Comparative Example 10 and Example 9 is that step (5) is different. Step (5) is changed to: placing the ceramic substrate in a muffle furnace, heating to 425°C at 2°C / min, pressurizing to 6.8MPa at 2Pa / s, maintaining the pressure for 1h, then releasing the pressure at 8Pa / s, heating to 860°C at 5°C / min, transporting the atomized droplets through a carrier gas, maintaining the temperature for 4.5h, and then placing in a vacuum furnace, heating to 1350°C at 10°C / min to obtain a conductive ceramic; the carrier gas is argon, and the carrier gas is 220mL / h; the atomized droplets are prepared by ultrasonic atomization of 5wt% LaCl3·7H2O-methanol at 20kHz, and the remaining steps are the same as Example 9.
[0056] Effect example
[0057] The following Table 1 shows the performance analysis results of conductive ceramics with different addition amounts using Examples 1 to 13 of the present invention, and the following Table 2 shows the performance analysis results of conductive ceramics using Example 9 of the present invention and Comparative Examples 1 to 10.
[0058] Table 1
[0059]
[0060] Table 2
[0061]
[0062] The ceramic slurry in the present invention is composed of aluminum oxide, titanium nitride and silicon dioxide of three different particle sizes, which improves the strength of the green body and reduces the possibility of deformation. At the same time, the amount of titanium nitride added is adjusted to adjust the ceramic resistivity, thereby achieving controllable resistivity of the ceramic. The present invention uses methyl methacrylate glycidyl ether and starch to form a gel skeleton, and uses amino-treated nano-graphite sheets as a skeleton structure support, which effectively reduces the volume shrinkage of the gel layer during the sintering process and ensures the mechanical strength of the ceramic. The ceramic slurry is used as the core material, and then a layer of gel is wrapped around the outer layer of the core material, and a three-stage high-temperature sintering treatment is performed to optimize the strength of the ceramic, while allowing the zirconium ions and nickel ions doped in the gel to combine with the lanthanum ions in the atomized liquid to form a zirconium-nickel-lanthanum-carbon crystal structure, which greatly improves the conductivity of the gel layer, thereby forming a uniform and continuous conductive path on the surface and inside of the ceramic.
[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a controllable resistivity conductive ceramic, characterized in that: The method comprises the following preparation steps: (1) Alumina balls with a ball diameter of 0.05-2 mm, titanium nitride with a particle size of 8-12 μm, and silicon dioxide with a particle size of 80-200 nm are fully mixed in a mass ratio of 1-99:1-99:0.1-5 to obtain ceramic powder; (2) Ceramic powder, anhydrous ethanol and alumina grinding balls are added into a ball mill equipped with a low-temperature plasma discharge device in a mass ratio of 3:3:
4. The ball mill is carried out at 50-100 rpm for 6 hours under an inert atmosphere. The low-temperature plasma discharge device is turned on every 2 hours and treated at 400-800 W for 1-5 minutes. The mixture is then poured into a low-speed stirring tank at a stirring speed of 5-10 r / min. A binder in an amount of 0.01-0.05 times the mass of the ceramic powder is added and the stirring time is 20-40 hours to obtain a ceramic slurry. (3) Starch and water are prepared into a concentration of 15-20 wt%, heated at 70-100°C and 30 rpm for 1-2 h, 0.08-0.1 times the mass of starch glycidyl methacrylate and 0.3-0.5 times the mass of starch in 20% sulfuric acid are added, stirring is continued for 4-6 h, and then 0.08-0.1 times the mass of starch amino-modified nanographite sheets are added, stirring is continued for 8-10 h, after cooling to room temperature, 0.08-0.3 times the mass of starch zirconium oxychloride and 0.08-0.1 times the mass of starch nickel acetate are added, stirring is continued for 1-3 h at 60 rpm, and then transferred to a 4°C refrigerator for 24 h to obtain a gel; (4) Inject the ceramic slurry into mold 1, freeze it at -25°C for 3 hours to obtain the core layer, and put it into the center of mold 2. The size of mold 2 is larger than that of mold 1. Fill the blank gap of mold 2 with gel, freeze it at -25°C for 10 hours, and then freeze-dry it at -50°C for 24 hours to obtain a ceramic matrix with the core layer wrapped by the gel layer; (5) The ceramic substrate is placed in a muffle furnace, heated to 400-430°C at a rate of 2-5°C / min, pressurized to 1.5-10MPa at a rate of 2-10Pa / s, maintained at pressure for 1-2h, then depressurized at a rate of 2-10Pa / s, heated to 800-860°C at a rate of 5-10°C / min, and atomized droplets are transported by a carrier gas, wherein the carrier gas is a mixture of H2O and O2, and the volume percentage of H2O is 1.3-8vol%, and the carrier gas is 50-300mL / h. The substrate is heat-treated for 3-5h, and then placed in a vacuum furnace, heated to 1200-1400°C at a rate of 8-10°C / min, to obtain a conductive ceramic; the atomized droplets are prepared by ultrasonic atomization of 5wt% LaCl3·7H2O-methanol at 20-60kHz.
2. The method for preparing a controllable resistivity conductive ceramic according to claim 1, characterized in that: The inert atmosphere in step (2) is nitrogen or argon.
3. The method for preparing a controllable resistivity conductive ceramic according to claim 1, characterized in that: The binder in step (2) is polyvinyl alcohol.
4. The method for preparing a controllable resistivity conductive ceramic according to claim 1, characterized in that: In step (2), the viscosity of the ceramic slurry is controlled at 100-500 cps.
5. The method for preparing a controllable resistivity conductive ceramic according to claim 1, characterized in that: The starch in step (3) is rice starch.
6. The method for preparing a controllable resistivity conductive ceramic according to claim 1, characterized in that: The preparation method of the amino-modified nano-graphite sheet in step (3) is as follows: nano-graphite sheets with a diameter of 1 to 100 μm and a thickness of 5 to 200 nm are selected and mixed with a 70 wt% ethanol aqueous solution to form a concentration of 0.1 wt%, the temperature is controlled at 60°C, a modifier is added in an amount of 5 to 20% by mass of the nano-graphite sheet, the mass ratio of γ-aminopropyl triethoxysilane to lauryl alcohol polyoxyethylene ether in the modifier is 1:1, the solid is filtered out after stirring at 1000 rpm for 2 hours, and dried at 80°C for 4 hours to obtain the amino-modified nano-graphite sheet.
7. The method for preparing a controllable resistivity conductive ceramic according to claim 1, characterized in that: In step (4), the radius difference between the core layer and the gel layer is controlled within a range of 0.1 to 5 mm.
Citation Information
Patent Citations
Preparation method for nano silicon-carbon composite electrode material of supercapacitor
CN103346026A
Aluminum oxide ceramic slurry for transformer frameworks and preparation method and application method thereof
CN112094109A
Cited By
Medical ceramic high-frequency electrotome
CN119430888A
A medical ceramic high-frequency electrosurgical unit
CN119430888B